2011
DOI: 10.1007/s00128-011-0238-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Testing of Waterborne Mercury with Red Sea Bream (Pagrus major) Embryos and Larvae

Abstract: Acute toxicity tests revealed that, in red sea bream (Pagrus major) embryos, 24 and 48 h LC(50) values of waterborne HgCl(2) were 67.3 and 39.1 μg Hg(2+) L(-1). In larvae, 48, 72 and 96 h LC(50) values were 41.9, 36.1 and 34.8 μg Hg(2+) L(-1), respectively. Sub-chronic toxicity tests indicated that mercury concentrations ≥20 μg Hg(2+) L(-1) decreased hatching success, increased mortality and induced teratogenicity in embryos and larvae. The NOEC, LOEC and MATC values were 8.0, 16.3 and 11.4 μg Hg(2+) L(-1) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Ismail and Yusof [13] observed that early life stages of Java medaka (O. for 96 h exhibited hooked tails, spinal malformations, and fin erosion. [60] Medaka (O. latipes) embryos exposed to 0.001-10 µM MeHg, HgCl 2 , α-HgS (Zhu Sha), and β-HgS (Zuotai) from 6 to 7 hpf to 10 dpf displayed abnormalities. [10] The reduction in the touchinduced escape response suggested that mercury had a detrimental impact on the hindbrain and spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Ismail and Yusof [13] observed that early life stages of Java medaka (O. for 96 h exhibited hooked tails, spinal malformations, and fin erosion. [60] Medaka (O. latipes) embryos exposed to 0.001-10 µM MeHg, HgCl 2 , α-HgS (Zhu Sha), and β-HgS (Zuotai) from 6 to 7 hpf to 10 dpf displayed abnormalities. [10] The reduction in the touchinduced escape response suggested that mercury had a detrimental impact on the hindbrain and spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Pollution of aquatic systems with mercury during the developmental stage, i.e., embryonic and larval phases, can impact the development of several fish organs, such as improper cardiovascular and eyeball growth and development (Huang W. et al, 2011). Since the infancy stage is the most vulnerable to mercury toxicity (Yoshimasu K. et al,2014), the majority of fish suffer damage at this stage because mercury can stimulate energy-intensive detoxifying processes and consume a substantial quantity of energy, which reduces the amount of energy that would otherwise be available for development (Sfakianakis D. et al, 2015).…”
Section: Bone Formationmentioning
confidence: 99%
“…The toxicity of methylmercury is several times that of inorganic mercury [14]. However, there is much controversy over whether inorganic mercury can be methylated inside fishes and converted to methylmercury [15,16,17]. Mercury is a highly toxic metal that is found in the spawning and nursery areas of red sea bream, and is believed to have deleterious effects on wild populations (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%